(untitled) (Konferensiyalar | Conferences, 2024)
This article delves into the intriguing evolution of English phonetics across different eras of English history. Phonetics, a field within linguistics, is essential for comprehending a language’s sounds and their historical development. The evolution of English phonetics, and the development of sounds and pronunciation patterns from the past to the current day will be explored with the help of this article. The journey of English phonetics also shows the intricate changes in pronunciation and sound patterns of today’s English language. English itself came from the Germanic language that has been heavily affected by Latin, French, and other languages over the centuries. That’s why today English sounds are the complex mixtures of different languages and their traditions. Studying the phonetic shifts in English over various historical epochs provides a significant understanding of the linguistic changes that have influenced the Modern English language.